Anticoagulant and Antithrombotic Actions of AVE5026, an Enriched Anti-Xa Hemisynthetic Ultra-Low-Molecular-Weight Heparin. (September 2014) - Hoppensteadt, Debra A.; Gray, Angel; Jeske, Walter P.; Walenga, Jeanine M.; Fareed, Jawed
Introduction: AVE5026 represents a new generation of ultra-low-molecular-weight heparin (LMWH) with high anti-Xa and low anti-IIa activities (anti Xa–IIa ratio >30). In addition, AVE5026 exhibits a relatively higher proportion of AT components. Materials and Methods: The anticoagulant, antiplatelet, antithrombotic, and bleeding effects of AVE5026 in comparison to other heparins were investigated in this study. Results: AVE5026 demonstrated weak effects in the global clotting assays; however, in the amidolytic anti-Xa assay, AVE5026 produced strong inhibitory effects. AVE5026 showed no cross-reactivity with the heparin-induced thrombocytopenia antibodies in the platelet aggregation system. AVE5026 produced a dose-dependent antithrombotic response after intravenous (IV) and subcutaneous (SC) administration in thrombosis models. The relative bleeding effects of AVE5026 in a rat tail bleeding and rabbit blood loss model were negligible after both IV and SC administration. Conclusions: This superior safety efficacy index in animal models in comparison with other LMWH may translate into improved antithrombotic efficacy with decreased bleeding risk.